Публічні закупівлі як підстава виникнення права державної власності - Кушнерук, Дмитро Володимирович; Кушнерук, Д. В.; Kushneruk, Dmytro (ВД "Гельветика", 2020)
У статті досліджуються особливості правового регулювання публічних закупівель як підстави виникнення права державної власності. Проаналізовано, у яких випадках для набуття державою права власності необхідно звертатися до процедури публічних закупівель. Здійснено порівняння старої та нової редакції Закону України «Про публічні закупівлі». Виявлено позитивні зміни у новій редакції Закону, а також недоліки, що залишилися. Запропоновано звертатись до європейського досвіду з метою вдосконалення правового регулювання процедури публічних закупівель.

The article explores the features of the legal regulation of public procurement as the basis for the emergence of state ownership. The importance of this procedure is explained by the fact that it was developed to combat corruption when using budget funds. One of the priorities facing Ukraine on the path to European integration is overcoming corruption. Implementation of the public procurement procedure brings Ukraine closer to European standards in the field of managing budget funds and acquiring state ownership of certain types of property which are necessary for the state needs. This procedure ensures competitiveness and transparency in the selection of suppliers, prevents the possibility of abuse by public funds managers. The positive effects of implementing this procedure are obvious. However, a new version of the law regulating public procurement has recently been adopted, which indicates the imperfection of the provisions that existed previously. In connection with the aforementioned, the article compares the old and new versions of the Law of Ukraine “On Public Procurement”. Positive changes in the new version of the Law, as well as remaining deficiencies were revealed. Among the positive changes can be noted a decrease in the threshold for the mandatory application of public procurement from 200 thousand UAH. up to 50 thousand UAH., the list of grounds for refusing to participate in the public procurement procedure, the introduction of a deadline for eliminating technical errors has been expanded. Among the remaining shortcomings, one can note the imperfection of the criteria for making decisions, the ability to establish requirements for specific suppliers, the ability to supply products that do not meet the requirements of the tender documentation. As a result of the analysis, it is proposed to turn to European experience in order to improve the legal regulation of public procurement. In particular, to revise the criteria for evaluating the goods to be procured, approaches to determining the specifications, take into account international standards for ensuring the environment and support for small and medium-sized enterprises. This is necessary because the state must not only take care of the efficient use of its property, but also comprehensively protect the rights and interests of its citizens.
Кушнерук, Д. В. Публічні закупівлі як підстава виникнення права державної власності / Д. В. Кушнерук // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 30-34.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; держава; право власності; публічні закупівлі; електронні закупівлі; тендер; спрощені закупівлі; state; property right; public procurement; electronic procurement; stender; simplified procurement